नेपालमा सूचना वर्गीकरणको उल्झन, सूचनाको हक कार्यन्वयनमा समस्या Confusion of information classification in Nepal, problems in implementation of right to information - पौडेल Poudel श्रीराम Shreeram (RR Interdisciplinary Journal, 2023)
Available with fulltext.